**Answer:**

kkkkkkkmkk

**Step-by-step explanation:**

kkkkkmkmkkkllkkmkkkkkkkkmkklkk

we have

we know that

If the point is an equation solution, it must satisfy the equation.

<u>case a</u>)

Substitute the values of x and y in the equation

-------> the point is not solution of the equation

<u>case b</u>)

Substitute the values of x and y in the equation

-------> the point is solution of the equation

<u>case c</u>)

Substitute the values of x and y in the equation

-------> the point is not solution of the equation

<u>case d</u>)

Substitute the values of x and y in the equation

-------> the point is not solution of the equation

therefore

<u>the answer is</u>

**The point is solution of the equation**

**Answer:**

the second steps was wrong.

**Step-by-step explanation:**

2x-8+3x+2=4x+10+3x-6

5x-6=7x+4

5x-7x=4+6

-2x=10

x=-5

**Answer:**

192.67

**Step-by-step explanation:**

588 - 3X = 10

Collect like terms

588 - 10 = 3X

578 = 3X

Divide through by 3

578/3 = 3X/3

X = 192.67 or